A RARE CASE OF SPONTANEOUS SUB-RETINAL HAEMORRHAGE ASSOCIATED WITH IDOPATHIC INTRACRANIAL HYPERTENSION - Pius, Chris; Pradeep, Thanuja (International Journal of Retina, 2023)
Introduction: Idiopathic Intracranial Hypertension (IIH)is defined as increase in intracranial pressure due to unspecified causes leading to headache, papilledema, and transient vision loss. Usually the patients present with mild visual loss but about 25% may develop permanent visual loss due to irreversible optic disc damage. One rare cause of severe visual loss is subretinal hemorrhage (SRH) due to underlying Subretinal Neovascular membrane. Case Report: We report a case of a 36-year-old man diagnosed with IIH and papilloedema with sudden onset profound visual loss in his right eye. On examination, there was a large peripapillary SRH superior to the disc and involving the macula.We stress the importance of recognizing this uncommon complication of papilledema and discuss the possible causes for developing SRH, its most common outcome and the diagnostic as well as treatment modalities available. Discussion: We stress the importance of recognizing this uncommon complication of papilledema and discuss the possible causes for developing SRH, its most common outcome and the diagnostic as well as current treatment modalities available. Conclusion: This report highlights a rare case of spontaneous sub retinal haemorrhage in a patient with IIH. Measurement of optic nerve sheath diameter can be a vital tool for the diagnosis of raised intracranial pressure in this setting.